Locus of control as critical moderator of the relationship between role stressors and intention to quit - Paulienė, Rasa; Tamaševičius, Virginijus; Diskienė, Danuta; Lazauskaitė, Monika; Thrassou, Alkis (Journal of Business Economics and Management, 2025)
This research examines how employees’ locus of control moderates the relationships between role conflict, role ambiguity, and intention to quit when assessing the mediation effects of counterproductive work behaviour and work engagement. A quantitative method (survey) was used for this study, with 348 questionnaires completed online. The research results reveal that, with a strong internal locus of control, work engagement mediates the relationship between role conflict and intention to quit and between role ambiguity and intention to quit. The higher the internal locus of control, the more both role conflict and role ambiguity affect work engagement, leading to intention to quit. Moreover, the manifestation of locus of control varies according to the employee’s level of education, age, field of activity, and the organisation size. The study is the first to develop an integrative framework, which depicts how team-level factors comprehensively affect interrelations between role stressors and employee intention to quit. Our research delineates, explicates, and directs crucial aspects of human resource management in organisations. It also highlights that in studying the employee behaviour, scholars should inexorably assess situations in the complex manner that research demands to delineate employee workplace behaviour stemming from a combination of personal, contextual, and circumstantial factors.